Farmers’ Perception on Cumin Based Intercropping Systems: A Case in Arid Zone of Rajasthan (Indian Journal of Extension Education, 2011)
In aberrant rainfall years, intercropping seems to be good preposition to sustain the production of cumin in rain-fed areas. Besides, in normal season, it increases the farm income and aims at efficient utilization of solar energy, moisture and nutrients. The present study was conducted in Pali district arid zone of Rajasthan. There are ten blocks in Pali district, out of which two blocks were selected by random technique from the identified district. Four villages were selected randomly from each identified block. For selection of respondents a total of one hundred thirty five farmers were selected from eight villages by proportionate random sampling. The respondents were further divided into three categories small, medium and large based on size of land holding. The most important intercropping system for the farmers of Pali district was cumin + gram and cumin + fenugreek. The farmers of the region were not aware of the recommended plant protection and production practices of cumin based intercropping systems. There is acute lack of transfer of technology efforts. Hence, the extension agency should take the lead role in transferring the research recommendations to the farmers of this area. Timely, availability of inputs like seed, fertilizer and plant protection chemicals are important for getting higher yield. Hence these may be taken by the policy makers/ extension agency and providing suitable price to cumin, gram and fenugreek will go a long way in sustaining these intercropping systems in the region. Also, certain researchable issues emerged from the study viz., development of suitable seed drill for ICS, determination of highly profitable row ratios and development of soil moisture conservation techniques for intercropping system. These issues may be given priority in research for developing the required technology for cumin based intercropping systems.